Data in, opportunities out.(Industry Trend or Event) - Fitter, Fawn (Computerworld, 1998)
Currently, most IT jobs in data mining are supporting rather than starring roles. However, that means there are more opportunities to break in. The 4 key roles for data mining experts are: 1. rapid application development, 2. technical architecture, 3. conversion and transformation, and 4. subject matter expertise. Rapid application development jobs call for IT pros with strong Visual Basic, PowerBuilder, client/server, and Web-based programming skills, as well as the ability to figure out what the end user wants and match it with tools available on the market. Technical architecture jobs tend to be at outside contractors rather than end-user companies. IT professionals with conversion and transformation skills design and implement the process of standardizing and conforming information from disparate systems.